A study of the factors that influence of paying zakat on income among staffs in Pejabat Tanah Jajahan Tumpat / Mohd Hafizzul Azmi Ismail - Ismail, Mohd Hafizzul Azmi (2012)
Zakat is one of the sources of funds available within the Islamic economic financial systems and has become a part of ijtima’l studies . Although it is obligatory for Muslims to contribute to zakat. However, the amount collected is relatively very small compared to the income tax collection. Hence, the purpose of this study is to investigate the zakat payment behavior among Government servants and thus tries to understand their underlying motivation. The objectives of this study are to determine the factors that influence of paying zakat on income among staffs in Pejabat Tanah Jajahan Tumpat, to analyze the service of quality that contribute the employees in government sector to pay zakat on income. To determine the promotion that influencing the payment of zakat on income among staffs in Pejabat Tanah Jajahan Tumpat and to know whether the zakat on income is an alternative to solving the social and economic problems. For the research methodology ,researcher developed questionnaire which use primary data. By having that data, the researcher uses the SPSS software to find and analyzed the result. The researcher use Multi Linear Regression model method to run the data and the result shows that promotion, has not significant relationship between the dependent variables while solving social and economic problems and service quality have a significant relationship between the influence of paying zakat on income among staff in Pejabat Tanah Jajahan Tumpat. . Then ,when use Pearson Correlation to test the hypotheses, show that all independent variables have significant with objective knowledge which promotion, solving social and economic problems and service quality